The effect of temperature during the hydrocracking of low-density polyethylene using a Ni-Cu/HZSM-5 catalyst - Suhailah Salma Maulida; Sri Kadarwati; Adid Adep Dwiatmoko; Egi Agustian (International Journal of Renewable Energy Development, 2026)
LDPE plastics contributed 20-30% of the plastics use. Due to its non-biodegradable properties, plastic waste management is crucial. In the other hand, the LDPE plastics provide potential and benefits in the exploration of energy resources; they could be converted to liquid fuels through a catalytic hydrocracking. This study focuses on the effect of temperatures during the hydrocracking of LDPE using a Ni-Cu/HZSM-5 catalyst. The Ni-Cu/HZSM-5 catalyst was synthesized using the wet impregnation method assisted by an ultrasonic irradiation. The characteristics of the catalyst were evaluated prior to its use during the hydrocracking of LDPE. This study showed that the impregnation of Ni and Cu at HZSM-5 surface did not significantly affect the crystallinity of HZSM-5. Even though the peaks of Ni and Cu in the diffraction pattern were not clearly observed, their presence at HZSM-5 surface was well confirmed by the XRF spectrum. In addition, the hierarchical structure of HZSM-5 was also confirmed by the appearance of microporosity together with the type-IV hysteresis loop on the nitrogen adsorption-desorption isotherm. A considerable decrease (~25%) of the catalyst acidity was observed after the impregnation of Ni and Cu at HZSM-5 surface. The Ni-Cu/HZSM-5 catalyst showed a good activity during the hydrocracking of LDPE at temperatures of 275−400 °C, resulting in liquid, solid, and gaseous products. The yields of the liquid product increased by increasing the hydrocracking temperatures. It was observed that by increasing the hydrocracking temperatures, the yield of the kerosene and diesel fractions decreased, while the yield of the gasoline fraction increased, as supported by the density and calorific value that was close to the commercial gasoline. A further temperature increase would lead to more products with lighter fractions, reducing the yield of gasoline. This was also supported by the presence of alkenes, ketones, and esters formed after the catalytic hydrocracking as shown by the FTIR spectra of the liquid products.